PENGARUH KESESUAIAN KOMPENSASI, MOTIVASI KERJA DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI KANTOR DESA SE KECAMATAN TASIK PUTRI PUYU - Ratna Ratna; Woro Utari; C. Sri Hartati (Universitas YPPI Rembang, 2023)
The purpose of this research is to test and analyze the impact of compensation, motivation and morale on the performance of Village Office employees in Tasik Putri Puyu District. The type of research carried out is Explanatory Research, the approach in this research uses a quantitative approach. In this research, the population determined is the employees of the Village Office in Tasik Putri Puyu Sub-district, which recorded as many as 88 people and sampling using a total sampling of 87 people. Research findings with a significance level of 5% are found if compensation has a significant impact on employee performance in the Village Offices in Tasik Putri Puyu District. This is evidenced by a significance value of 0.026. Work motivation has a significant impact on the work results of employees in the Village Offices in Tasik Putri Puyu District. This is evidenced by a significance value of 0.0186. Morale has a significant impact on the performance of employees in the Village Offices in Tasik Putri Puyu District. This is evidenced by a significance value of 0.000.Key words: Compensation, Motivation, Enthusiasm, Performance